Case Report: Telitacicept in severe myasthenia gravis: a case study with multiple autoantibodies - Guo, Qian; Huang, Yusen; Wang, Fangruyue; Fang, Le (Frontiers in Immunology, 2023)
Multi-antibody-positive myasthenia gravis (MG) presentations are relatively rare, often found in older patients, and generally predict a poor prognosis. We report a case of a female patient with generalized MG, testing positive for Titin antibodies (Titin-Ab), ryanodine receptor antibodies (RyR-Ab), and acetylcholine receptor antibodies (AChR-Ab), and resistant to acetylcholinesterase inhibitors. Following unsuccessful traditional therapies, she received Telitacicept, leading to significant improvements. This case underscores Telitacicept's potential efficacy for similar patients and offers insights into the clinical characteristics of multi-antibody MG.